An embedded cryptossystem implementing symmetric cipher and public-key crypto algorithms in hardware [compact disc] - Hau, Yuan Wen, 1980- (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2005